Effect of Using Additive to Microbiology Activities of Mozzarella Cheese Storage at Refrigerator Temperature - Wildan Yudha Prasetyo; Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2011)
The aims of this study were to determine the best preservative between potassium sorbate, sodium benzoate, and chitosan on the microbiological quality of Mozzarella cheese stored at refrigerator temperature. The results showed that the addition of preservatives potassium sorbate, sodium benzoate, and chitosan did not give a significantly different effect (P> 0.05) on the TPC, total number of molds, and total number of yeasts of Mozzarella cheese. Storage time of Mozzarella cheese that nested on the type of added preservatives did not give a significantly different effect (P>0.05) on the TPC and total number of yeasts but gave a significantly different effect (P<0.05) on the number of molds of Mozzarella cheese. Based on the research data, it can be concluded that the utilization of preservative potassium sorbate, sodium benzoate, and chitosan were effective in suppressing the growth of microorganisms. Potassium sorbate tends to be more effective in suppressing the growth of microorganisms in Mozzarella cheese stored at refrigerator temperature. Key words: whey, texture, fat, organoleptic, nata de milko